CALLUS INDUCTION INCREASE OFTRIGONELLA FOENUM-GRAECUM L. BIOMASS ACCUMULATION INDIFFERENT MEDIUM BY 2,4-D AND BA - M., Masara D. J.; Neamah , S. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This investigation was carried out to determine the role of the plant growth regulators 2,4-Dichlorophenoxyacetic acid (2,4-D) and 6-Benzyladenine (BA) added to the media culture LS and B5 in the biomass accumulation of induced callus culture from the cotyledonous of Trigonella foenum-graecum L. different concentrations of 2,4-D at 4.0, 8.0 and 12.0 µM and BA at 0.0, 2.0, 4.0, 6.0 and 8.0 µM were tested. The surface sterilization of seeds showed that it is possible to rely on a concentration of 2.0% of NaOCl for 5 min to obtain sterile seedlings. The results also indicated that there was a significant effect of the growth regulators 2,4-D and BA added to the LS medium, as the interaction between the two concentrations of 12.0 µM of 2,4-D and 4.0 µM of BA recorded the highest means value of callus formation response (CFR), the shortest duration for the Start callus induction (SCI) and complete callus formation (CCF). At the same time, the interaction between 8.0 µM of 2,4-D and 6.0 µM of BA recorded the highest fresh weight (FW), dry weight (DW) and relative humidity (RH) for calli. The B5 medium, the interaction between the two concentrations of 8.0 µM of 2,4-D and 2.0 µM of BA recorded the highest means value of CFR. In contrast, the treatment with a concentration of 12.0 µM of 2,4-D with the control treatment of BA showed the lowest duration of callus induction initiation.